Призрачные огни: [роман] / Дин Кунц - Кунц Дин Р. (Почерк мастера, 2001)
Экземпляры: аб. (2012) / Инвентарный номер: 54921 / Цена: 172.59 / Сис.шифр: 84(7Сое)-44 / Авт.знак: К 91 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44